The synthesis of [14C]AZD5122. Incorporation of an IV 14C‐microtracer dose into a first in human study to determine the absolute oral bioavailability of AZD5122. (12th May 2016) - Hickey, Michael J.; Allen, Paul H.; Kingston, Lee P.; Wilkinson, David J.
Abstract : AZD5122, N ‐(2‐(2, 3‐difluorobenzylthio)‐6‐((2 R, 3 R )‐3, 4‐dihydroxybutan‐2‐ylamino)pyrimidin‐4‐yl)azetidine‐1‐sulfonamide was under investigation as a potential chemokine receptor CXCR2 antagonist for the treatment for inflammatory diseases. To gain a better understanding of the human pharmacokinetic profile, an exploratory phase I IV microtracer study was conducted using carbon‐14 radiolabelled AZD5122. [ 14 C]AZD5122 was carbon‐14 labelled in the pyrimidine ring in five steps in an overall radiochemical yield of 19% from [ 14 C]thiourea. The absolute oral bioavailability of AZD5122 was assessed in healthy subjects by an oral administration of AZD5122, followed by a concomitant intravenous [ 14 C]AZD5122 microdose. Abstract : In support of a medicinal chemistry programme aimed at developing antagonists of the CXCR2 receptor, the synthesis carbon‐14 labelled AZD5122 from [ 14 C]thiourea is described. [ 14 C]AZD5122 was used in an IV microtracer study to gain a better understanding of the human pharmacokinetic profile.